THE EFFECT OF RABBIT DANCE LEARNING TO INCREASE GROSS MOTOR ABILITY OF CHILDREN WITH MILD MENTAL RETARDATION IN ELEMENTARY SPECIAL SCHOOL. - Fuaida, Nadiya Sholikhatul (JPK (Jurnal Pendidikan Khusus), 2024)
ABSTRACT This research aims to find out the influence of rabbit dance learning to improve gross motor skills of children with mild mental retardation in Elementary Special School. The approachment that used in this research is a quantitative approach with a experiment Single Subject Research (SSR). The research design that used was A-B-A design with a total 3 sessions on Baseline-1 (A1), 7 sessions on intervention session (B), and 3 sessions on Baseline-2 (A2). The subjects of this research was a children with mild mental retardation in grade 4 elementary school at Elementary Special School. The data collection technique in this research was by observation, while the analysis technique that used descriptive statistical technique. The results of the research showed that rabbit dance learning can improve gross motor skills of children with mild mental retardation. The improvement was obtained from the results of the test instrument consisting of aspects strength, agility, speed, coordination and balance. The increase was shown in the change in mean level from Baseline-1, which is 50.3 to Baseline-2, which is 65.7. Based on the skor, the conclusion from this research that rabbit dance learning can improve gross motor skills of children with mild mental retardation at Elementary Special School.